Meningkatkan Kreativitas dan Minat Belajar Anak-Anak di Sekitar Kantor Camat Batang Onang dengan Belajar Bersama dan Membuat Keterampilan - Ilham Dhani Hasibuan; Gusti Pirandy (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
The author conducted practicum II at the Batang Onang Sub-District Office, North Padang Lawas. The Field Work Practice aims to improve students' skills in developing mindsets, adding ideas and insights so that later they will produce a skilled and quality workforce. Apart from that, street vendors are one of the embodiments of the Tri Dharma of Higher Education, namely Service. Through these street vendors, it is hoped that students will be able to make a good contribution to society. The second practicum conducted by the author was to examine the problems experienced by children in the village of Pasarmatanggor. This paper intends to review the problem of the lack of interest in learning and children's creativity and the solution. Interest in learning is a very important factor in the success of children. Because, the role of interest is very big influence on a person's willingness to accept and perform an action. In addition, children must be trained to be creative. Through the creative process, children will gain confidence thanks to their achievements in getting things done. This provision can help them form imaginative and inventive mindsets in the future.